307 Identification and differential expression of microRNAs in the testis of chicken with high and low sperm motility. (7th December 2018) - Sun, Y; Liu, Y; Li, Y; Bai, H; Ni, A; Chen, J
Abstract: Sperm motility is one of the most important indicator for evaluating roosters' fecundity. However, the molecular regulation underlying chicken sperm motility is not yet clear. MicroRNA (miRNA) plays epigenetic roles in reproduction. In this study, we compared the testicular miRNAs of Beijing-you roosters with high (HS) and low (LS) sperm motility using Solexa sequencing. Length distribution analysis showed that the dominant size of the small RNAs detected in the testis was 24 28 nt. In total, 518 known and 106 novel miRNAs were identified. A number of 23 miRNAs were found differentially expressed ( P < 0.05, |log2 fold change| ≥ 1) between the HS and LS, including 18 known and five novel miRNAs. Function enrichment of predicted target genes of the differential miRNAs indicated that the differentially expressed miRNAs were involved in the pathways of GnRH signaling, MAPK signaling, and Wnt signaling. The miRNA-gene interaction network revealed two key candidate miRNA-gene pairs that may affect chicken sperm motility viz gga-miR-155/KCNA1 and gga-miR-7480-5p/AHI1. qRCR was also used to further validate their expression. The results here provide deep insight into the expression of miRNA in the testis of chicken and suggest their roles in sperm motility regulation.